Early intervention with acupuncture improves the outcome of patients with Bell's palsy: A propensity score-matching analysis - Yang, Lian-Sheng; Zhou, Dan-Feng; Zheng, Shu-Zhen; Zhao, Bai-Ming; Li, Huo-Gui; Chen, Qi-Qing; Zhong, Yun; Yang, Hong-Zhi; Zhang, Kun; Tang, Chun-Zhi (Frontiers in Neurology, 2022)
Objective Although acupuncture is widely used as a complementary therapy in the treatment of Bell's palsy (BP) when to initiate acupuncture is still controversial. This study aims to determine the efficacy of the early intervention by acupuncture on BP. Methods We retrospectively gathered clinical data from the Third Affiliated Hospital of SUN-YAT SEN University between 2016 and 2021. We selected newly diagnosed patients with BP who were diagnosed by registered neurologists or acupuncturists formally. The qualified patients were divided into two groups according to whether or not initial acupuncture treatment was given within 7 days from the onset of palsy. Cohorts were balanced using 1:1 propensity score matching (PSM). Cox proportional hazards modeling and Kaplan–Meier analysis were applied to determine the differences between the two groups. The outcome included time to complete recovery of facial function, the rate of complete recovery, and the occurrence of sequelae in 24 weeks. Results A total of 345 patients were eligible for this study and were divided into the manual acupuncture/electroacupuncture (MA/EA) group (n = 76) and the EA group (n = 125). In the propensity score-matched cohort, the time to complete recovery was significantly shorter in the MA/EA group compared with the patients in the EA group (hazard ratio 1.505, 95% CI 1.028–2.404, p <0.05). The MA/EA group had a higher rate of favorable outcomes at 12 weeks than the EA group (93.4 vs. 80.3%, p = 0.032), and the occurrence of sequelae at 24 weeks showed a greater reducing trend in the MA/EA group than the EA group (6.6 vs. 16.4%, p = 0.088). Conclusion Acupuncture intervention at the acute stage of BP could shorten the time to recovery and improve the outcome. Clinical trial registration http://www.chictr.org.cn, identifier ChiCTR 2200058060.